Genealogie in der Moderne : Akteure - Praktiken - Perspektiven. - Hecht, Michael; Timm, Elisabeth (Berlin/München/Boston : Walter de Gruyter GmbH, 2022)
How was knowledge produced by different people in different times and at different places? How was knowledge stored, managed, classified, organized, deployed, forgotten, and recycled? Finally, how did such practices affect what counted as knowledge? The series invites contributions on the 'long' early modern period in Europe and publishes also works on global cultures of knowledge under European influence.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books